(untitled) (Oratio Directa, 2022)
This study examines the communication motives of citizen journalists who contributed to the Citizen6 channel on Liputan6.com. It uses a qualitative descriptive approach based on observation and interviews conducted at the Liputan6.com editorial office on 29 July 2017. The participants comprised a community-development manager and three citizen contributors with student and private-sector employee backgrounds. The analysis relates participants' accounts to Maslow's hierarchy of needs, particularly belonging, esteem, and self-actualization. The findings identify six related motives: pursuing a writing interest, improving skills, sharing useful information, learning from sources, expanding social relations, and gaining pride or recognition from published work. Self-actualization is the dominant interpretive category, while esteem appears through personal pride and public recognition. Citizen6 also functions as an editorial intermediary: contributors can submit everyday stories and feature articles, whereas sensitive or hard-news material is redirected for more specialized verification. The study describes the motives of three contributors in a specific editorial setting; it does not represent all Citizen6 contributors or measure audience effects.